Post-COVID-19 hyperhidrosis and tachycardia syndrome (Research, Society and Development, 2022)
The pandemic caused by the new coronavirus SARS-CoV-2, COVID-19, has impacted the world scenario, worsening morbidity and mortality rates. Among the persistent symptoms of COVID-19, called Long Covid (CL) or Post Covid Syndrome (PCS), neurological manifestations are of significant importance due to their association with the worsening of the clinical condition of patients. Among the complications observed in critically ill patients, Paroxysmal Sympathetic Hyperactivity (SPH) stands out, characterized by sudden symptoms of increased sympathetic tone. The aim of this study was to report a case of HSP in a patient with post-COVID-19 hyperhidrosis and Postural Orthostatic Tachycardia Syndrome (STOP), to which a treatment protocol consisting of laserpuncture and myofascial release was applied at the outpatient clinic of a public hospital in Teresina-PI. For data collection, the instruments Depression Anxiety Stress (DASS-21), Mini Mental State Examination (MMSE), Nordic Musculoskeletal Symptom Questionnaire (NSO), Quality of Life Assessment Questionnaire (WHOQOL-BREF), Pittsburgh Sleep Quality (PSQI), Visual Analog Scale (VAS) and Algometry. The results showed a reduction in tachycardia, hyperhidrosis, level of stress, anxiety and depression, a decrease in muscle pain, an increase in the Painful Perception Threshold (PDL) with a consequent reduction in withdrawal from routine activities, impacting on the improvement of the general quality of life and the sleep. It is concluded that the treatment by laserpuncture and myofascial release was effective in the symptoms of HSP and consequent improvement in the patient's quality of life.